Analysis of Young Farmer Regeneration, MSME Incubation, and Supply Chain Systems on the Sustainability of Agricultural MSMEs in East Java - Hernawati, Hernawati; Silamat, Eddy; Supriandi, Supriandi (Westscience Press, 2025)
This study analyzes the influence of young farmer regeneration, MSME incubation, and supply chain systems on the sustainability of agricultural MSMEs in East Java. Using a quantitative approach, 140 respondents were surveyed with a Likert scale (1–5), and the data were processed with Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results show that all three variables positively and significantly affect sustainability, with young farmer regeneration being the most influential factor, followed by supply chain systems and MSME incubation. The coefficient of determination (R² = 0.430) indicates that 43% of sustainability can be explained by the model, while the predictive relevance (Q² = 0.415) demonstrates strong predictive validity. These findings suggest that sustainability of agricultural MSMEs requires generational renewal, robust supply chain systems, and incubation support to enhance competitiveness and long-term resilience. This study contributes to the literature by integrating human resource regeneration, institutional incubation, and supply chain perspectives as drivers of MSME sustainability in the agricultural sector.